Introduction to biomaterials : basic theory with engineering applications - Agrawal, C. Mauli 1959-; Ong, Joo L.; Appleford, Mark R.; Mani, Gopinath (Cambridge texts in biomedical engineering, 2014)
"This textbook gives students an introduction to the world of biomaterials, linking the fundamental properties of metals, polymers, ceramics and natural biomaterials to the unique advantages and limitations surrounding their biomedical applications. Clinical concerns such as sterilization, surface modification, cell-biomaterial interactions, drug delivery systems, and tissue engineering are discussed in detail, giving students practical insight into the real-world challenges associated with biomaterials engineering; key definitions, equations and concepts are concisely summarised alongside the text, allowing students to quickly and easily identify the most important information; and bringing together elements from across the book, the final chapter discusses modern commercial implants, challenging students to consider future industrial possibilities. Concise enough to be taught in a single semester, and requiring only a basic understanding of biology, this balanced and accessible textbook is the ideal introduction to biomaterials for students of engineering, materials science and medicine"- Resumé vydavatel